Coverage rates and timeliness of nationally recommended vaccinations in Swiss preschool children: A descriptive analysis using claims data. Issue 6 (5th February 2020) - Schneider, Rahel; Reinau, Daphne; Schur, Nadine; Blozik, Eva; Früh, Mathias; Signorell, Andri; Heininger, Ulrich; Schwenkglenks, Matthias; Meier, Christoph R.
Highlights: Proportions of children with up-to-date vaccinations increased over time. National vaccination goals have not been reached in Swiss preschool children. Delays of vaccine administration relative to age-appropriate standards were common. Measles-mumps-rubella vaccine was the most frequently delayed basic vaccination. Every twenty-fifth child did not receive any vaccination up to 25 months of age. Summary: Background: Low vaccination coverage as well as incomplete and delayed vaccinations pose a risk for the individual and population protection from vaccine-preventable diseases. Aim: To describe vaccination patterns for nationally recommended basic and supplementary vaccinations in Swiss preschool children. Methods: We performed a descriptive study based on administrative claims data from a large Swiss health insurer (Helsana), in cohorts of children born between January 2010 and December 2016. We assessed coverage rates of nationally recommended basic vaccinations (i.e., diphtheria, tetanus, acellular pertussis [DTaP], Haemophilus influenzae type b [Hib], poliomyelitis [IPV], measles, mumps, and rubella [MMR]) and supplementary vaccinations (i.e., pneumococcal conjugate vaccine [PCV] and meningococcal group C conjugate vaccine [MCV]) for each birth cohort at the age of 13, 25, and 37 months. Additionally, we analysed timeliness of vaccinations using inverse Kaplan-Meier curves. Results were extrapolated to the Swiss population. Results: The study population comprised 563, 216 children. We observed continuously increasing coverage rates for all vaccinations until the 2015 birth cohort. Overall, up-to-date status for the first dose of studied vaccinations at 37 months was as follows: DTaP: 95.4%; Hib: 94.9%; IPV: 95.5%; MMR: 86.8%; PCV: 83.2%; and MCV: 66.7%. On average, however, only seven out of ten children had an up-to-date status for completed basic vaccinations; even less (six out of ten) were up-to-date for recommended supplementary vaccinations at 37 months of age. Moreover, 4% of all analysed children received none of the recommended vaccinations and there were substantial regional differences. Delays in vaccine administration were common. The most frequently postponed basic vaccination was MMR; 22.6% of children vaccinated with the first dose experienced delays relative to age-appropriate standards. Conclusion: To avoid future outbreaks and transmission of vaccine-preventable diseases, vaccination coverage in Switzerland must be further improved. In addition, more emphasis should be placed on timely vaccination.